CHAQ2020 - Seymourön - Spatiala data - CHAQ2020 - Seymourön - Rådata - Westin, Jonathan; Almevik, Gunnar (Swedish National Data Service, 2021)
The first Swedish Antarctic Expedition (1901-1903), led by Otto Nordenskjöld, sailed to Antarctica on the ship Antarctic captained by CA Larsen, and established a research station on Snow Hill Island. There six members overwintered and performed paleontological, meteorological, geomagnetic and geological studies, while the rest of the expedition set sail for South Orkney. After the winter, on the way back to Snow Hill Island, the Antarctic got stuck in the ice and sank. At this point, the expedition members were divided into three groups. One of these overwintered an extra year on Snow Hill Island, whereas the other two groups were forced to build stone huts in order to overwinter at Hope Bay and Paulet Island. An Argentinean vessel, the Corbeta Uruguay, rescued the expedition in November 1903. CHAQ 2020 is an Argentinean-Swedish project with fieldwork in the area around the Antarctic Peninsula aiming to investigating and documenting the historical remains of the first Swedish South Polar expedition under the leadership of Otto Nordenskjöld 1901-1903. The material was collected in January and February 2020. This catalogue entry collects the spatial data from Seymour Island, which include point clouds and textured meshes produced through structure-from-motion photography. The structure-from-motion documentation of the monuments consists of four complete sets of photographic raw data captured with a Fujifilm X-T2 on January 4-6, 2020. The remains of the boat were fragile and therefore difficult to stage in a way that prevented morphological changes between documenting the two sides. The photos were captured by Gunnar Almevik. Syftet med forskningsprojektet var att dokumentera lämningarna efter Otto Nordenskjölds Antarktisexpeditionen 1901-1903. Materialet består av fotografier, planer, ritningar, 3d-modeller och drönarfilmer från Snow Hillön, Hoppets vik och Seymourön. Denna katalogpost samlar den spatiala datan från Seymourön, vilket inkluderar punktmoln och texturerade trådmodeller skapade genom ...